Financial Distress and Tax Avoidance: The Moderating Role of Managerial Ownership in IDX Listed Indonesian Agricultural Product Firms - Andreano, Carlo; Permatasari, Intan Kurnia (Integrative Perspectives of Social and Science Journal, 2026)
This study examines the effect of financial distress on tax avoidance and the moderating role of managerial ownership in agricultural companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach, this study analyzes 96 firm-year observations from 32 firms through panel data regression with a random-effects model. Tax avoidance is measured by Cash Effective Tax Rate, financial distress by the Altman Z-Score, and managerial ownership by the proportion of shares held by management. The results show that financial distress does not significantly affect tax avoidance. In contrast, managerial ownership significantly increases tax avoidance and significantly moderates the relationship between financial distress and tax avoidance by weakening the effect of financial distress. Among the control variables, profitability has a significant negative effect on Cash ETR, indicating higher tax avoidance among more profitable firms, while firm size has a marginal positive effect and leverage is insignificant. Overall, the findings suggest that managerial ownership plays an important role in shaping tax strategies among Indonesian agricultural firms, whereas financial distress alone does not significantly influence tax avoidance behavior.